Pengaruh Kecerdasan Emosional, Pola Asuh Demokratis, dan Kecerdasan Interpersonal Terhadap Sikap Remaja - Andi Patimbangi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
The aim of this study was to determine the effect of emotional intelligence, democratic parenting, and interpersonal intelligence of adolescent attitudes regarding free sex. The researcher used ex post facto method. The polulation was all students of MAN 1 Kajuara Bone Regency. While sample taken random sampling technique. The resercher used Structural Equation Modeling (SEM), namely AMOS program which has the aim to test a series of relationships